Reflections on science as a gendered endeavour: changes and continuities - Amâncio, L. (Social Science Information, 2005)
This article aims to show, first, that gender representations are embedded in the organizational forms and dominant culture of science and, second, that scientists and scientific institutions have contributed to the perpetuation of gender representations, in particular the representation of women as a sexed category. The theoretical framework of this analysis articulates studies on gender and science with the theory of social representations. Three periods will be considered to illustrate the argument: first, the period of exclusion of women from science in the late 19th and early 20th centuries; second, the period of the development of women's and gender studies in the 1960s and 1970s; and finally, the implications of the past for the present, discussed in the light of recent changes.